2000
DOI: 10.1111/j.1447-0756.2000.tb01196.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Perinatal Outcome of Pregnancies after the Age of 45

Abstract: Women aged 45 years or more at delivery may expect a good pregnancy outcome but should expect a higher incidences of placental abruption, placenta previa, preeclampsia and caesarean delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
2
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 7 publications
3
43
2
2
Order By: Relevance
“…Placenta previa occurred in 9% cases and the results are comparable to a study by Gilbert 9 et al which showed 10-fold increased risk of placenta previa in elderly gravidae. This is slightly higher when compared to a study by Abu-Hieja et al 10 where the incidence was 4.4%. Abruption occurred in 2% cases and 1% controls.…”
Section: Discussioncontrasting
confidence: 63%
“…Placenta previa occurred in 9% cases and the results are comparable to a study by Gilbert 9 et al which showed 10-fold increased risk of placenta previa in elderly gravidae. This is slightly higher when compared to a study by Abu-Hieja et al 10 where the incidence was 4.4%. Abruption occurred in 2% cases and 1% controls.…”
Section: Discussioncontrasting
confidence: 63%
“…Protection of the pelvic floor is a frequently cited reason for requesting a caesarean section and the basis on which the female obstetricians in London in the previously mentioned study made their choice. 7 The belief that childbirth inevitably damages the pelvic floor, and that caesarean sections can effectively prevent subsequent incontinence, prolapse and sexual dysfunction, is often tempered by strong cultural and peer pressures. There is controversy surrounding the etiology of pelvic floor dysfunction arising after pregnancy, and the cause of this may relate to pregnancy rather than labour and delivery.…”
Section: Why Do Women Prefer Caserean Sectionmentioning
confidence: 99%
“…Yet, 69% of obstetricians would perform a caesarean section for maternal request. 7 This can only mean that the obstetricians believe that the risks of caesarean section are so close to the risks of labour and vaginal delivery that maternal choice can be allowed to influence this decision.…”
Section: Medicolegal and Ethical Issuementioning
confidence: 99%
See 1 more Smart Citation
“…As evidências indicam também que gestantes com estatura abaixo de 150cm, idade nos extremos do ciclo reprodutivo, isto é, menor que 19 anos ou superior a 30 anos e gravidez gemelar ou com morbidades associadas requerem acompanhamento específico e frequente dos profissionais de saúde no âmbito dos programas de atenção à gestante, com o objetivo de evitar o desfecho inadequado da gravidez 2,[12][13][14][15] . Entende--se também que as gestantes na faixa etária de 19 a 30 anos com diagnóstico antropométrico pré-gravídico de eutrofia também merecem atenção especial dos programas de atenção pré-natal.…”
unclassified